Struma ovarii with Hashimoto’s thyroiditis: case report and review of the literature - Tan, Huayun; Zhang, Tingting (Frontiers in Medicine, 2024)
Background Struma ovarii, a rare ovarian neoplasm originating from germ cells within mature teratomas, typically manifests benign characteristics. However, instances of malignant transformation have been documented. Case description This report discusses a 25-year-old woman who had surgery in May 2020 to remove teratomas from both ovaries. In 2023, an ultrasound showed a complex mass in her pelvis. Further imaging tests, including CT, MRI, and F-18 FDG PET/CT scans, along with high levels of the CA 125 protein, suggested a mass in her left ovary, initially thought to be ovarian cancer. However, a closer examination after surgery found thyroid tissue and several types of cell growth but no cancer, confirming the diagnosis of struma ovarii. The pathology of hypermetabolic thyroid nodules on F-18 FDG PET/CT confirmed Hashimoto’s thyroiditis. Conclusion This case underscores the importance of considering struma ovarii in the differential diagnosis of ovarian masses, especially in patients with a history of teratomas. It highlights the challenges in distinguishing struma ovarii from ovarian cancer due to similar clinical signs and imaging. Struma ovarii can be associated with Hashimoto’s thyroiditis.